Specific inhibition of long-lasting, L-type calcium channels by synthetic parathyroid hormone. - Pang, P K (1990)
The effect of an active synthetic N-terminal fragment of bovine parathyroid hormone (bPTH), bPTH-(1-34), on Ca2+ channels was studied in mouse neuroblastoma cells (N1E-115). With the whole-cell variation of the patch-clamp technique, T (transient) and L (long-lasting) types of Ca2+ currents were identified. Pharmacological characterization showed that the L current was amplified by the Ca2+ channel stimulator BAY K-8644, but the T current was unaffected. The administration of bPTH-(1-34) produced dose-related inhibition of the L current, which could be reversed by BAY K-8644. The peptide had no effect on the T current. In addition, use of the fluorescent indicator fura-2 showed that bPTH-(1-34) inhibited the KCl-stimulated increase in intracellular free Ca2+ in neuroblastoma cells with L channels but not in cells with T channels. An inactivated (oxidized) preparation of bPTH-(1-34) failed to affect the L current. High-affinity binding of labeled PTH analog to these neuroblastoma cells was also demonstrated. In addition, bPTH-(1-34) inhibited the L current in cultured vascular smooth muscle cells from rat tail artery. These data indicate that, in some tissues, PTH can act as an endogenous blocker of Ca2+ entry.